Clinical Phenotype of DiGeorge Syndrome with Negative Genetic Tests: A Case of DiGeorge-Like Syndrome?. (17th December 2015) - Laccetta, Gianluigi; Toschi, Benedetta; Fogli, Antonella; Bertini, Veronica; Valetto, Angelo; Consolini, Rita
Abstract : We report a case of DiGeorge-like syndrome in which immunodeficiency coexisting with juvenile idiopathic arthritis, congenital heart disease, delay in emergence of language and in motor milestones, feeding and growing problems, enamel hypoplasia, mild skeletal anomalies, and facial dysmorphisms are associated with no abnormalities found on genetic tests.